Hippo in smooth muscle - a therapeutic target in vascular diseases driven by aging and hypertension - Albinsson, Sebastian; Rippe, Catarina; Daoud, Fatima; Bastrup, Joakim Armstrong; Holmberg, Johan; Jepps, Thomas A.; Swärd, Karl (Frontiers in Physiology, 2025)
IntroductionThe Hippo signaling pathway is a key regulator of cellular growth and organ size, acting through the transcriptional coactivators YAP and TAZ. These proteins shuttle between the nucleus and cytoplasm in response to Hippo pathway activity, which, when active, leads to cytoplasmic sequestration and degradation of YAP/TAZ, preventing them from initiating gene transcription. Although initially studied in development and cancer, recent research has revealed crucial functions for YAP and TAZ in the adult vascular wall.Scope of the reviewThis review discusses emerging insights into the roles of Hippo signaling and its downstream effectors YAP and TAZ in adult vascular smooth muscle cells (SMCs) and endothelial cells (ECs), with an emphasis on their physiological and pathological relevance.Key findingsIn SMCs, YAP and TAZ are vital for maintaining contractile identity by regulating expression of SMC contractile proteins. Inducible deletion of YAP/TAZ in adult SMCs results in impaired contractility, hypotension, and spontaneous arterial aneurysms. Despite these findings, the role of upstream Hippo signaling in SMCs remains poorly understood, and its therapeutic potential is underexplored. In ECs, YAP and TAZ respond to disturbed flow patterns by promoting a pro-atherogenic gene expression profile, contributing to increased atherosclerotic burden in hypercholesterolemic conditions.Discussion and conclusionTargeting Hippo-YAP/TAZ signaling in vascular cells represents a promising yet complex strategy for treating vascular diseases. The key challenge lies in achieving precise, cell-specific, and temporally controlled modulation that enhances beneficial effects, such as aneurysm protection and arterial repair, while minimizing off-target or adverse effects in non-vascular tissues.